Utilization of Educational Reports in Improving Teacher Performance and School Quality at SD Negeri 2 Purbowangi - Harnani, Muji Aris; Saryanto, Saryanto (Malikussaleh University, Aceh, Indonesia, 2025)
Implementing education report cards still faces challenges, such as low data literacy, limited internet access, and lack of intensive training for teachers and principals. Most schools have not utilized education report card data optimally. Many schools do not systematically utilize education report card data in a real action plan. This article aims to determine how using education report cards improves teacher performance and school quality at SDN 2 Purbowangi. This research method uses a qualitative descriptive approach with a case study design. Using education report cards with the right strategy can improve teacher performance and school quality at SDN 2 Purbowangi. Using data in education report cards helps educational units identify problems, set priorities, determine root causes, and design programs relevant to problem indicators systematically and in a structured manner. Success in reading educational report card data into concrete actions gives educational units definite steps to improve school quality. Teacher training programs, workshops, In House Training (IHT) can improve teacher performance. However, this study also shows several obstacles, such as a lack of knowledge in interpreting data, less fundamental root cause data, and many misconceptions between principals and teachers. Schools are expected to form a special team responsible for supporting the use of educational report cards.